An Application Of Inner Product Spaces " Conditioning And the Rayleigh Quotient " (Journal of Humanitarian and Applied Sciences, 2017)
في هذه الورقة سندرس تطبيق عملي لفضاء الضرب الداخلي , وكيف يستخدم لحل مجموعة من المعادلات على الصورة :AX=b  .m×1  متجه من الرتبة  b ,   m×n  مصفوفة  من الرتبة A  حيث
Keywords: Inner Product Spaces; Conditioning; Rayleigh Quotient